Recent advances in metal-free catalysts for the remediation of antibiotics, antibiotic resistant bacteria (ARB), and antibiotic resistant genes (ARGs). Issue 29 (5th July 2022) - Wang, Ziqian; Du, Chunyu; Ding, Dahu; Chen, Rongzhi; Yang, Shengjiong; Cai, Tianming
Abstract : This paper summarizes recent advances in metal-free catalysts for the remediation of antibiotics, antibiotic resistant bacteria (ARB), and antibiotic resistant genes (ARGs). Abstract : Metal-free catalyzed advanced oxidation processes (AOPs) are state-of-the-art technologies with high oxidation capabilities for wastewater purification, taking advantage of the synergies of direct adsorption and the generated reactive oxygen species (ROS). Typically, carbonaceous functional materials exhibit satisfactory efficiencies for eliminating organic contaminants by coupling with various chemical oxidants ( e.g., hydrogen peroxide, persulfates, permanganates, peracetic acid, ferrates, and periodates). This paper summarizes recent advances in the applications of metal-free catalyzed AOPs to remove organic pollutants and elucidates the underlying mechanisms. First, we briefly introduce the traditional and newly emerging metal-free catalysts. Second, a detailed comprehensive overview of the current state-of-the-art progress in metal-free catalyzed AOPs for wastewater purification is provided, emphasizing their efficiencies and the mechanisms involved. Special attention is paid to removing antibiotics, and the inactivation of antibiotic resistant bacteria (ARB) and antibiotic resistant genes (ARGs), respectively. Finally, the current challenges and possible future perspectives are outlined based on the above discussion. Overall, this review may shed new light on metal-free catalyst induced AOPs for environmental remediation.